Investigate on computer-aided fixture design and evaluation algorithm for near-net-shaped jet engine blade. (June 2020) - Wu, Dongbo; Zhao, Bing; Wang, Hui; Zhang, Kaiyao; Yu, Jie
Abstract: This study proposes a computerized framework for computer-aided fixture design and evaluation for near-net-shaped jet engine blades. First, the manufacturing process of near-net-shaped jet engine blades and requirements for the fixture design and evaluation were analyzed. Second, a numerical model of the positioning error and the corresponding experimental platform were established. Third, a mechanical model of the blade under cutting conditions was analyzed, a finite element model (FEM) was established. Fourth, a mathematical model of the machining fixture layout optimization was established, and the positioning clamping points of the machining fixture were optimized by the combination of finite element analysis (FEA) and genetic algorithm. Finally, the corresponding algorithm verification was carried out by positioning error and cutting experiments. The results showed that the proposed computerized framework could evaluate and optimize the fixture of the same type blade to obtain the positioning and mechanical behavior of the fixture, and can realize high-precision manufacturing of near-net-shaped jet engine blades.